Immunoproteasome acted as immunotherapy ‘coffee companion’ in advanced carcinoma therapy - Shi, Shaoyan; Ou, Xuehai; Liu, Chao; Wen, Hao; Jiang, Ke (Frontiers in Immunology, 2024)
Immunoproteasome is a specialized form of proteasome which plays a crucial role in antigen processing and presentation, and enhances immune responses against malignant cells. This review explores the role of immunoproteasome in the anti-tumor immune responses, including immune surveillance and modulation of the tumor microenvironment, as well as its potential as a target for cancer immunotherapy. Furthermore, we have also discussed the therapeutic potential of immunoproteasome inhibitors, strategies to enhance antigen presentation and combination therapies. The ongoing trials and case studies in urology, melanoma, lung, colorectal, and breast cancers have also been summarized. Finally, the challenges facing clinical translation of immunoproteasome-targeted therapies, such as toxicity and resistance mechanisms, and the future research directions have been addressed. This review underscores the significance of targeting the immunoproteasome in combination with other immunotherapies for solid tumors and its potential broader applications in other diseases.